Modification of Business Strategy Through The Application of Circular Economy in Coffee Shop Business Units in Pontianak City: Case Study of Four Coffee Shops - Mahardika Agung Madepo; Lina Budiarti; Faaiza Soraya Khalida (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: The increasing number of coffee shops in Pontianak every year makes competition even tighter. These conditions require the development of alternative strategies, especially by adopting environmentally based strategies.Purpose: This study aims to analyze the choice of modern coffee shop strategy, to analiyze strategy development by adding the circular economy concept to it, and to analyze the sustainability of the circular economy-based strategy that will be implemented.Design/methodology/approach: This study uses qualitative research with interactive analysis techniques and SWOT analysis to develop the strategies. The respondents of this study are four coffee shop owners. The study was conducted for six months in May – November 2023.Findings/Result: The study reveals that although all four coffee shops have a low understanding of circular economy-based strategies, they have unintentionally implemented some of these practices. The main priority of the identified strategies is to increase awareness of the circular economy. These strategies are then developed by integrating elements like eco-friendly packaging, recycled materials, and digital technology.Conclusion: Modern coffee shops in Pontianak are shaped by the owners' diverse backgrounds and focus on sustainability. Koffiestelsel, Segitiga Coffee, Saca Coffee, and Tumbuh Coffee each take different approaches to eco-friendly practices. A SWOT analysis suggests strategies at three levels: corporate, business, and functional.Originality/value (state of the art): This study explore the implementation circular economy concept on business strategy especially in smaller scale business. Keywords: environmental, modern coffee shop, strategy development, sustainability, SWOT analysis